Visual Inspection dan Pengujian Tahanan Isolasi Pemutus Tenaga (PMT) Bay 150 KV Kopel - Nur Afifah; Ulinnuha Latifa (Universitas Islam Lamongan, 2021)
Electrical energy is a primary need to supply all aspects of community needs andactivities for electricity. For this reason, maintenance is carried out to improve efficiency, quality, and distribution of electrical power. The PMT at thesubstations is used as a mechanical switch or as a circuit breaker. The methodused in this study was qualitative and quantitative to determine the presence of anomalies in electrical distribution. Based on in service/visual inspection, the condition of the equipment is good visually, and there is no anomalies were found. Testing at an insulation resistance, the rise and fall of the measurement results can be caused by several factors such as the wrong position of the measuring instrument, a dirty insulator body, or high humidity levels.